Loss of adult visual responses by developmental BPA exposure is correlated with altered estrogenic signaling - Annastelle Cohen; Avery Sherffius; Jennifer S. Jensen; Rebecca Harris; Elizabeth Burch; Gregory Foster; Stephen MacAvoy; Mikayla Delbridge-Perry; Victoria P. Connaughton (Communications Biology)
Abstract Early exposure to environmental contaminants such as bisphenol A (BPA) poses significant health risks due to their potential to disrupt development. However, many studies focus on immediate effects, leaving the long-term impact poorly understood. Here, we investigate the long-term effects of transient BPA exposure during critical periods of visual system development in zebrafish (Danio rerio). We exposed zebrafish to BPA at 72 hours post-fertilization (hpf) and 7 days post-fertilization (dpf) and assessed retinal anatomy, optomotor responses, retinal physiology, and molecular signaling pathways during juvenile or adult stages. Photopic ERGs from adults revealed changes to bipolar and photoreceptor cell responses that were differentially affected by exposure age and BPA concentration. Exposure to low (0.001 µM) BPA at 72 hpf, not 7 dpf, altered expression of estrogen-responsive genes cyp19a1b and esr2 in adult retinas, as well as the thyroid-responsive gene thrb. We also identified changes in phosphorylation levels of the intracellular kinases Akt, ERK, and JNK in adult retinas and found differences depended upon BPA concentration and exposure age. This study demonstrates that brief early life exposure to BPA can have profound and lasting effects on the visual system, identifying a novel effect of this well-known chemical.